Balloon dilatation and outcome among patients undergoing trans-femoral aortic valve replacement. (1st March 2017) - Fink, Noam; Segev, Amit; Kornowski, Ran; Finkelstein, Ariel; Assali, Abid; Rozenbaum, Zach; Vaknin-Assa, Hana; Halkin, Amir; Fefer, Paul; Ben-Shoshan, Jeremy; Regev, Ehud; Konigstein, Maayan; et al.
Abstract: Background: Balloon pre-dilatation before transcatheter aortic valve replacement (TAVR) is performed at the discretion of the treating physician. Clinical data assessing the implications of this step on procedural outcomes are limited. Methods: We conducted a retrospective analysis of 1164 consecutive TAVR patients in the Israeli multicenter TAVR registry (Sheba, Rabin, and Tel Aviv Medical Centers) between the years 2008 and 2014. Patients were divided to those who underwent balloon pre-dilation ( n  = 1026) versus those who did not ( n  = 138). Results: Rates of balloon pre-dilation decreased from 95% in 2008–2011 to 59% in 2014 ( p for trend = 0.002). Baseline characteristics between groups were similar except for more smoking (22% vs. 8%, p  = 0.008), less past CABG (18% vs. 26%, p  = 0.016), less diabetes mellitus (35% vs. 45%, p  = 0.01), and lower STS mortality scores (5.2 ± 3.7 vs. 6.1 ± 3.5, p  = 0.006) in the pre-dilatation group. The pre-dilation group included less patients with moderate to severely depressed LVEF (7% vs. 16%, p  < 0.001) and higher aortic peak gradients (76.9 ± 22.7 mmHg vs. 71.4 ± 24.3 mmHg, p  = 0.01). Stroke rates were comparable in both groups (2.5% vs. 3%, p  = 0.8), but pre-dilation was associated with lower rates of balloon post-dilatation (9% vs. 26%, p  < 0.001). On multivariate analysis, balloon pre-dilatation was not a predictor of device success or any post-procedural complications ( p  = 0.07). Conclusions: Balloon pre-dilatation was not associated with procedural adverse events and may decrease the need for balloon post-dilatation. The results of the present study support the current practice to perform liberally balloon pre-dilatation prior to valve implantation.